2020
DOI: 10.1177/0194599820924621
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Quality of Systematic Reviews and Meta‐analyses Published in High‐Impact Otolaryngology Journals

Abstract: Objective To assess the methodological quality of intervention-focused systematic reviews (SRs) and meta-analyses (MAs) published in high-impact otolaryngology journals. Data Sources Ovid Medline, Embase, and Cochrane Library. Review Methods A comprehensive search was performed for SR and MA citations from 2012 to 2017 in the 10 highest impact factor otolaryngology journals. Abstracts were screened to identify published manuscripts in which the authors indicated clearly that they were performing an SR or MA. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 244 publications
1
6
0
1
Order By: Relevance
“…53 Moreover, Martinez-Mondero et al concluded that "over 50% of these SRs and MAs had weaknesses in at least 3 of the 16 items in the AMSTAR-2." 54 Taken together, our findings are consistent with the existing literature across multiple disease processes within otolaryngology and other medical specialties. This issue can potentially be addressed by having journal editors require submission of the AMSTAR-2 checklist alongside the SR.…”
Section: Discussionsupporting
confidence: 90%
“…53 Moreover, Martinez-Mondero et al concluded that "over 50% of these SRs and MAs had weaknesses in at least 3 of the 16 items in the AMSTAR-2." 54 Taken together, our findings are consistent with the existing literature across multiple disease processes within otolaryngology and other medical specialties. This issue can potentially be addressed by having journal editors require submission of the AMSTAR-2 checklist alongside the SR.…”
Section: Discussionsupporting
confidence: 90%
“…To aid in evaluating the quality of meta-analyses, a number of critical appraisal tools are now available (eg, A Measurement Tool to Assess Systematic Reviews 2, AMSTAR 2) 12. Applied in a variety of areas of biomedical research, these tools have provided empirical evidence for areas of improvement in future meta-analyses, yet no reviews exist within the context of CPSP 13–15…”
Section: Introductionmentioning
confidence: 99%
“…Issues involved in meeting the standards for seven review components (identified in bold in Table 4.1) are addressed in detail. These were chosen for elaboration for one (or both) of two reasons: 1) The component has been identified as potentially problematic for systematic review authors based on consistent reports of their frequent AMSTAR-2 or ROBIS deficiencies (Gagnier & Kellam, 2013;Kolaski et al, 2021;Martinez-Monedero et al, 2020;Pussegoda et al, 2017;Riado Minguez et al, 2017;Tsoi et al, 2020); and/or 2) the review component is judged by standards of an AMSTAR-2 "critical" domain. These have the greatest implications for how a systematic review will be appraised: if standards for any one of these critical domains are not met, the review is rated as having "critically low confidence.…”
Section: Acronym Year Linkmentioning
confidence: 99%